SVETOTRANZISTOR - T. A. Ismailov; H. M. Gadjiyev; S. M. Gadjiyevа; T. D. Nezhvedilov; T. A. Chelushkina (Вестник Дагестанского государственного технического университета: Технические науки)
In this article the opportunity to form a pn-junction bipolar transistor as a light-emitting, which will increase the degree of integration of large scale integrated circuits by reducing heat gain.